Development of Liveworksheets-Based E-LKPD Using the Discovery Learning Model on Reaction Rate Topic for High School Students - Chintya Eglesyes; Destria Roza (Universitas Lampung, 2025)
This research aims to develop a Liveworksheets-based E-LKPD integrated with the Discovery Learning model on reaction rate material for Grade XI students and to determine its validity and practicality. This study employed a Research and Development (R&D) approach using the Four-D (4D) model, which consisted of the Define, Design, and Develop stages. The product was evaluated by one material expert and two media experts, while a limited field trial was conducted with 58 students at SMA Negeri 14 Medan. Data were collected using validation sheets and student response questionnaires and were analyzed descriptively. The results showed that the material expert gave a validity score of 88.7%, and the media experts gave 89.6%, resulting in an overall validity score of 89.15%, categorized as very valid. The limited field trial obtained a practicality score of 76.84%, indicating that the E-LKPD was practical and acceptable for classroom use. Students reported that the interactive features, structured Discovery Learning stages, and multimedia elements helped improve their understanding of reaction rate concepts. Overall, the developed E-LKPD is considered valid and practical, making it a suitable digital learning resource to support chemistry learning and enhance student engagement. Further research is recommended to implement the product on a larger scale to evaluate its effectiveness on learning outcomes